From professional competences to market qualifications in the construction industry - Ireneusz Woźniak; Jakub Kus (Edukacja Ustawiczna Dorosłych)
The constructionsector supports the building of the Integrated Qualification System (ZSK) through the participation of its representatives in many initiatives aimed at improving the matching of professional competences and qualifications to the needs of the sector. The Sector Competence Board in Construction will soon receive the instrument in the form of the Sectoral Qualifications Framework in Construction (SRK-Bud) – legislative works are underway to include SRK-Bud into ZSK – which will facilitate the development of new qualifications in line with the sector's needs. As a part of the INFODORADCA+ project, the information about 63 professions from the construction sector will be developed. Content-rich descriptions of these professions can be used to prepare applications for the inclusion of new market qualifications to ZSK. It has startedin 2017,when the first construction qualification – ”Construction joinery assembling” – was included into ZSK as a market qualification. The first certificates confirming the achievement of learning outcomes in this qualification were issued in the second half of 2018. Similarity and complementarity of occupational information included in the model for the description of a profession within the INFODORADCA+ project as well as in the application form for the inclusion of a new market qualification to ZSK fosters the acceleration of works on the development of new market qualifications for the construction sector.